N-(2,6-Dichlorophenyl)benzamide - Gowda, B. Thimme (International Union of Crystallography, 2008)
The conformation of the N—H and C=O bonds in the structure of the title compound (N26DCPBA), C(13)H(9)Cl(2)NO, are anti to each other, similar to that observed in N-phenylbenzamide (NPBA), N-(2-chlorophenyl)benzamide (N2CPBA), N-(2,3-dichlorophenyl)benzamide (N23DCPBA) and other benzanilides. The asymmetric unit of N26DCPBA contains two molecules. The bond parameters in N26DCPBA are similar to those in NPBA, N2CPBA, N23DCPBA and other benzanilides. The amide group, –NHCO–, makes a dihedral angle of 30.8 (1)° with the benzoyl ring in the first molecule and 35.1 (2)° in the second molecule of the asymmetric unit. The dihedral angle between the two benzene rings (benzoyl and aniline) is 56.8 (1)° in the first molecule and 59.1 (1)° in the second molecule. N—H⋯O hydrogen bonds give rise to infinite chains running along the a axis of the crystal structure.